Framing Indigenous Leadership - Long, Joseph E. (Advances in Social Sciences Research Journal, 2017)
The concept of framing is critical to the study of leadership and sensemaking across organizations. This paper examines framing from the unique military context of American Special Forces leading indigenous people of developing countries in combat. Specifically, I identify several deficiencies in the extant leadership literature that remains insufficient for understanding the unique context of indigenous leadership. I explain how the process of framing helps with sensemaking for both American and indigenous forces to include how framing can be understood as a vehicle for conserving, generating and transforming current indigenous leadership practices. I conclude with a theoretical framing construct that suggests how framing indigenous leadership using follower-centric models can help transform American leadership into micro-level social movements capable of creating collective identity.